2022
DOI: 10.1155/2022/6207701
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Based Metabolomics Profiling of High-Risk Human Papillomavirus and their Emerging Roles in the Progression of Cervical Cancer

Abstract: High-risk human papillomavirus (HR-HPV) is the main etiological factor for cervical cancer. Accumulating evidence has suggested the active role of metabolites in the initiation and progression of cancers. This study explored the plasma metabolic profiles of HPV-16 positive (HPV16 (+)), HPV-18 positive (HPV18 (+)), and HPV negative (CTL) individuals using a nontargeted metabolomics approach. C8 ceramide-1-Phosphate (d18 : 1/8 : 0) was found to inhibit cervical cancer cell proliferation and migration in vitro, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 52 publications
3
3
0
Order By: Relevance
“… 64 Decreased concentrations of aspartyl‐hydroxyproline have been observed in the plasma of patients with human papillomavirus during the progression of cervical cancers. 65 Our study reinforces the connection between hydroxyprolyl‐hydroxyproline and L‐alpha‐aspartyl‐L‐hydroxyproline and proline metabolism in oral tumors in dogs. Future research should explore potentially related proteins and pathways, such as gelatinolytic and prolidase activity, as referenced in studies of breast cancer.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“… 64 Decreased concentrations of aspartyl‐hydroxyproline have been observed in the plasma of patients with human papillomavirus during the progression of cervical cancers. 65 Our study reinforces the connection between hydroxyprolyl‐hydroxyproline and L‐alpha‐aspartyl‐L‐hydroxyproline and proline metabolism in oral tumors in dogs. Future research should explore potentially related proteins and pathways, such as gelatinolytic and prolidase activity, as referenced in studies of breast cancer.…”
Section: Discussionsupporting
confidence: 84%
“…These alterations in collagen metabolism, coupled with increased enzymatic activities, may signify tissue remodeling characteristic of the invasive phenotype, potentially promoting metastatic dissemination in breast cancer 64 . Decreased concentrations of aspartyl‐hydroxyproline have been observed in the plasma of patients with human papillomavirus during the progression of cervical cancers 65 . Our study reinforces the connection between hydroxyprolyl‐hydroxyproline and L‐alpha‐aspartyl‐L‐hydroxyproline and proline metabolism in oral tumors in dogs.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The LDL receptors on the surface of malignant tumor cells are very sensitive to cholesterol, as well as with a substantial increase in the demand for cholesterol by malignant tumor tissues, which results in elevating the levels of LDL that carry cholesterol [ 33 ]. This study [ 34 ] is the first to identify C8-ceramide-1-phosphate as an important lipid metabolite that modulates cervical cancer cell function. In addition, they also identified that other lipids, such as LysoPC and PC, may also involve cervical cancer progression, requiring further investigation.…”
Section: Metabolic Changes In Cervical Cancermentioning
confidence: 99%